Du tourisme au développement durable : Les usages des cours d’eau par les kayakistes français - Antoine Marsac (VertigO)
This article redraws the main stages of evolution of the sensibilities in the nature within the framework of the activity canoeing in France. The approach combines a historical survey of entering the training arrangements for sports and tourism practices, and a sociological survey which parallels the nature of uses on sites unevenly urbanized. Crossing sources - excerpts of interviews and archives of the Canoe Club - aims to identify key environmental issues encountered during rivers trips. During Second World War, french kayakers adapt arrangements of mills for the training to the competition of slalom. But the drying up of streams due to the construction of hundreds of deductions makes it difficult to change in activity from the post-war period. The contemporary period is characterized by conflicts in the access to the water, in spite of agreements signed with the fishermen and of construction of artificial sites in big cities. Having now realize the harmful effects of dams and pollution on the ecosystems of rivers, kayakers adapt their actions to the imperative of sustainable development. But the protection of the play area via the preservation of sufficient debits remains the main preoccupation for them.